Low frequency of HER2 expression in colorectal cancer: A Tunisian single-center study: HER2 expression in colorectal cancer - Ben Lazreg, Khouloud; Majdoub, Wiem; Bdioui, Ahlem; Krifa, Marwa; Lajmi, Zaineb; Belkacem, Oussema; Alaya, Mariem; Mestiri, Sarra; Hmissa, Sihem; Missaoui, Nabiha (Cellular and Molecular Biology, 2025)
HER2 expression is a potential theranostic and prognostic marker in some cancers, particularly in breast and gastric cancers. However, published data on HER2 expression in colorectal cancer (CRC) remain controversial. This study investigates the immunohistochemical and molecular expression of HER2 in primary CRC and evaluates its clinicopathological and prognostic significance in Tunisian patients. A retrospective analysis was conducted on 144 CRC patients. HER2 status was assessed by immunohistochemistry and tissue microarray analysis, following the diagnostic criteria for gastroesophageal adenocarcinoma. CRC cases with ambiguous results underwent chromogenic in situ hybridization. The mean patient age was 61.9 years (male-to-female ratio: 1.18:1). Tumors were classified as colonic (74.3%) or rectal (25.7%), with 45.8% located in the left colon. Stage III disease was identified in 37.5% of cases, and distant metastases were present in 13.9%. HER2 expression results were as follows: negative (score 0/1+) in 142 cases (98.6%), equivocal (score 2+) in one case (0.7%), and overexpressed (score 3+) in one case (0.7%). No HER2 gene amplification was detected, and none of the metastatic CRC cases showed HER2 immunostaining. These findings suggest that HER2 overexpression and amplification in CRC are rarer than previously reported, highlighting the need for multicenter Tunisian studies to validate these results. The variability in HER2 immunostaining criteria further underscores the importance of a standardized scoring system to ensure consistency in both diagnosis and research.